ENTRE BAQUETAS E TAMBORINS: CARTOGRAFIAS DA AFIRMAÇÃO DE UM MODO SENSÍVEL DE SE CONSTITUIR MULHER NUMA ESCOLA DE SAMBA - Campos, Carla de Souza (2021)
The research addresses the experience of a woman in the Capixaba Percussion Orchestra and her trajectory in the samba school drums. The objective of the work was to know and analyze the effects of the practices of rupture with patriarchal-capitalistic subjectivation processes that capture the desiring production of becoming a woman. We started this study to answer the questions: What are the effects of the practices of rupture with patriarchal-capitalistic subjectivation processes that capture the desiring production of becoming women in the tambourine wing of the Capixaba Percussion Orchestra? What are the practices instituted in the Capixaba Percussion Orchestra that do not collaborate to give way to the desiring production and that strengthen the macho practices? What are the effects of the instituting practices in the relationships of the members of the Capixaba Percussion Orchestra? What do they inaugurate? What do they highlight? What are the effects of the problematizing, reflective, dialogical practices of the women of the Capixaba de Percussão Orchestra in the constitution of another way of relating to the context of the samba school? We conducted an intervention research to map the breeding practices that were being established. We carry out the analysis of the discourse, seeking to escape the interpretation of the data to collaborate with an analysis of the practices that give way to the institutional force in the relationships. The data show that playing as a woman in the city of Vitória, in the community of Caratoíra, within the Escola de Samba Novo Império, means “to endure the stride” of overcoming racial obstacles, sexist in addition to the common socioeconomic challenges among those who live on the outskirts of Brazilian capitals. The work of black women in the samba school highlights the urgency of cracks or breaches where it is possible to escape and create strategies of resistance and powers, institutional movements, of collective life.